2012
DOI: 10.1016/j.gene.2012.07.070
|View full text |Cite
|
Sign up to set email alerts
|

Campylobacter fetus subspecies: Comparative genomics and prediction of potential virulence targets

Abstract: The genus Campylobacter contains pathogens causing a wide range of diseases, targeting both humans and animals. Among them, the Campylobacter fetus subspecies fetus and venerealis deserve special attention, as they are the etiological agents of human bacterial gastroenteritis and bovine genital campylobacteriosis, respectively. We compare the whole genomes of both subspecies to get insights into genomic architecture, phylogenetic relationships, genome conservation and core virulence factors. Pan-genomic approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
54
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 68 publications
2
54
0
Order By: Relevance
“…genomes, reported that it contains 552 gene families (Ali et al, 2012;Lefébure and Stanhope, 2009). This latest study included only one C. fetus subsp.…”
Section: Venerealismentioning
confidence: 99%
See 4 more Smart Citations
“…genomes, reported that it contains 552 gene families (Ali et al, 2012;Lefébure and Stanhope, 2009). This latest study included only one C. fetus subsp.…”
Section: Venerealismentioning
confidence: 99%
“…fetus genomes (ATCC19438 and 82-40 respectively) and estimated from these that the C. fetus sp. core genome contains 1 628 gene families (Ali et al, 2012;Fouts et al, 2005;Stynen et al, 2011).…”
Section: Venerealismentioning
confidence: 99%
See 3 more Smart Citations